PERBEDAAN SELF-CARE AGENCY BERDASARKAN TEORI DOROTHEA OREM ANTARA TIPE NUCLEAR FAMILY DAN AGING COUPLE FAMILY - Kurniati, Mei Fitria (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Nurses as a part of health workers have an important role in changing the patients and families bahavior that able to balance and independence in their self care activities. One of the family functions is to have health care fuctions which is to maintain the family’s condition in order to have high productivity.The purpose of this study is to knowThe differences of self-care agency based on the Dorothea Orem’s Model between Nuclear family and aging couple family types. This research design was usedCross Sectional. The sampling methode usedwas Purposive Sampling. The number of sampling was 30 families which is nuclear family and aging couple family. The independentvariables isself-care agency and the dependent variable are Nuclear family and aging couple family types.Data were collected using questionnaire and analyzed by using Independent t-test with significance level was 0,05. The result showed that the average value of self care agency for nuclear family was 2387,40 while for aging family was 2163. The result of Mann Whitney showed sig. ρ = 0,000 that means ρ